2019
DOI: 10.1016/j.btre.2019.e00328
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genomic analysis of Zymomonas mobilis ZM4 mutants with enhanced ethanol tolerance

Abstract: Highlights Z. mobilis ER79ag and ER79ap ethanol mutants were obtained by adaptive evolution. ER79ap had a better cell viability than the WT and ER79ap under ethanol stress. Mutants shared SNVs in clpP and spoT / relA , in addition ER79ap has a SNP in clpB . Mutant allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Recently, Pallach et al reported that one of the two cell surface exopolysaccharides in Z. mobilis , the galactose containing polymer (PS1), may have a crucial role in ethanol tolerance ( Pallach et al, 2018 ). Another study in two ethanol-tolerant mutants exhibited that clpP , spoT / relA , and clpB genes seem to contribute to the ethanol tolerance in Z. mobilis ( Carreon-Rodriguez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Pallach et al reported that one of the two cell surface exopolysaccharides in Z. mobilis , the galactose containing polymer (PS1), may have a crucial role in ethanol tolerance ( Pallach et al, 2018 ). Another study in two ethanol-tolerant mutants exhibited that clpP , spoT / relA , and clpB genes seem to contribute to the ethanol tolerance in Z. mobilis ( Carreon-Rodriguez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol toxicity becomes the primary problem for its production via microbial fermentation [40]. Numerous studies have been conducted to find, modify, and construct an optimal host with high tolerance to ethanol [9,41]. While the construction of an ethanol biosynthesis pathway in several heterologous hosts has been reported, the major obstacle limiting their achievement is due to the low tolerance of the host to ethanol toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Applying this method in Z. mobilis results in introducing two mutant strains with high capability to tolerate ethanol concentrations of more than 70–90 g/l. These two mutants were designated as ER79ag and ER79ap that both have a mutation in clpP , clpB , and spot/relA gene; however, the position of mutations in these two strains were different [ 124 ]. ClpB is an ATP-dependent chaperone that belongs to the Hsp100-family and is a member of the AAA (ATPase associated with diverse cellular activities) chaperone.…”
Section: Introductionmentioning
confidence: 99%